Clinical aspects of the incident of dermatophytoses in the State of Sergipe, Brazil (Research, Society and Development, 2021)
Dermatophytosis demonstrates a worlwide prevalence, especially in children and adults from tropical and subtropical areas. Epidemiological studies have highlighted three main genera as the most common for affecting approximately 20% of the world population: Trichophyton, Microsporum and Epidermophyton. This study aimed to evaluate the number of cases of dermatophytosis in the state of Sergipe from 2014 to 2017. Therefore, a documentary, cross-sectional and prospective study was performed to detect dermatophyte cases in Sergipe, taking into account the following aspects: mycological diagnoses by municipality of residence, sex and anatomical sites. Data was acquired from Central Public Health Laboratory of Sergipe (LACEN) in the same period. The results of the analyzes showed that among the 1386 mycological exams, the number of female patients was significantly higher compared to males, however male cases positive for dermatophytosis were higher, 51.4%. Another aspect that exhibited greater results was the age group between 0-5 and 6-10 years (18.04% and 17.07%, respectively). As for the municipalities of residence of the studied patients, Aracaju demonstrated the majority of the cases. Concerning the infection sites, there was a predominance of the scalp (20.73%), followed by the lower limbs (23.90%) and nails (15.60%). Moreover, it is noted that such results were relevant, as the panorama of this non-compulsory notification disease in the municipalities of the state of Sergipe was elevated. Finally, these results encourage the need for interventions that provide improvements in public health as well as in the social field through the adoption of preventive measures and sanitary actions.